Bilateral Popliteal Artery Entrapment Syndrome: An Approach to Diagnosis and Salvage - Aman Berry Williams (Case Reports in Vascular Medicine)
Popliteal artery entrapment syndrome (PAES) is a rare cause of limb-threatening vascular disease. Usually, it arises from aberrant embryological development or acquired dysfunctionality of the popliteal artery and its surrounding musculotendinous structures in the popliteal fossa. Here, we present a case report of a young woman with relatively sudden-onset short-distance claudication and paraesthesia affecting her right leg primarily. She had no recent traumatic history and no atherosclerotic risk factors and was otherwise previously very active. She had a feeble right popliteal artery pulse and no foot pulses. Nerve conduction studies demonstrated no electrophysiological abnormalities. Following computed tomography angiography and magnetic resonance imaging, it was determined she had type 2 PAES. Subsequently, the patient underwent surgical division of a lateralised head of her medial gastrocnemius, resection of her fibrosed popliteal artery, and repair with a reversed long saphenous vein interposition graft. Following surgery, her symptoms resolved, and she remains on aspirin and ultrasound surveillance.